2008
DOI: 10.1149/1.2817518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of OH Radicals on Formation of Cu Oxide and Polishing Performance in Cu Chemical Mechanical Polishing

Abstract: The amount of OH radicals generated varied according to the complexing agent or Cu ion, and the accelerating effect of OH radicals on the rate of Cu oxide formation was found in acidic pH. When Cu͑I͒ ions and oxalic acid were added to H 2 O 2 -based slurry, the decreases in etch and removal rates of Cu were observed because more generation of OH radicals resulted in the formation of thicker Cu oxide compared to additive-free slurry. Therefore, proper control of the formation and dissolution of Cu oxide led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The plasma‐ethanol interface is also known to produce radicals leading to the formation of hydrogen peroxide (H 2 O 2 ) and we have confirmed that also in our case H 2 O 2 is produced and consumed by equation (see Supporting Information) . The interaction of locally produced (i.e., close to the interface) H 2 O 2 with reduced copper atoms then leads to the formation of CuO, where the very high reaction rates of solvated electrons and the non‐acidic state (>6 pH; measured before and after synthesis, see Supporting Information) prevents Fenton‐like reactions with the Cu‐ions . The size of the NPs is then determined by the local concentration of coalescing CuO.…”
Section: Resultssupporting
confidence: 83%
“…The plasma‐ethanol interface is also known to produce radicals leading to the formation of hydrogen peroxide (H 2 O 2 ) and we have confirmed that also in our case H 2 O 2 is produced and consumed by equation (see Supporting Information) . The interaction of locally produced (i.e., close to the interface) H 2 O 2 with reduced copper atoms then leads to the formation of CuO, where the very high reaction rates of solvated electrons and the non‐acidic state (>6 pH; measured before and after synthesis, see Supporting Information) prevents Fenton‐like reactions with the Cu‐ions . The size of the NPs is then determined by the local concentration of coalescing CuO.…”
Section: Resultssupporting
confidence: 83%
“…The citric acid and H 2 O 2 are well-known as a complexing agent and oxidizer, respectively. The combination has been effectively used for chemical mechanical polishing (CMP) of Cu [27,28]. Following etching, the specimens were rinsed with 18 M cm DI water, dried with N 2 gas flow, and then immediately immersed into the plating bath with the potential applied.…”
Section: Methodsmentioning
confidence: 99%
“…Oxalic acid produced a thicker oxide film than the citric-acid-based solution or H 2 O 2 -only solution. 19 The stress determined by the measurement of the wafer curvature is biaxial stress, which is intrinsically gener-ated from the chemical modification. During the polishing process, the pressure to push the wafer to the pad was applied normal to the surface.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18] The differences could induce different polishing rates according to the slurry pH, oxide formation character differences, and deviations in the radical formation rate. 19 However, there has been little research into the correlation between the difference in oxide formation and the corrosion character of various slurries. In this research, the stress evolution due to the oxide formation by the slurry and its effect on the corrosion fit generation was intensively studied.…”
mentioning
confidence: 99%